2019
DOI: 10.3389/fvets.2019.00031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Unowned Domestic Cat Management in the Urban Environment of Rome After 30 Years of Implementation of the No-Kill Policy (National and Regional Laws)

Abstract: Law no. 281, enacted by the Italian Parliament in 1991, was the first that aimed at managing urban free-roaming cats living in colonies, without killing and/or moving them from their site. It had been anticipated by the Lazio Regional Law no. 63/1988 and subsequently refined by the Lazio Regional Law no. 34/1997. These laws introduced: (i) the cats' right to live free and safe; (ii) the compulsory neutering of cats by the Veterinary Services of the Local Health Unit; (iii) the institutionalization of cat caret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 4 publications
0
26
0
1
Order By: Relevance
“…Perhaps the results attained on the UCF campus over a 28-year period most closely resemble what occurred contemporaneously on the waterfront in Newburyport, Massachusetts, where a long-term TNR program eliminated a population of an estimated 300 resident cats over a 17-year period; due to ongoing management, the results attained there have persisted over the ensuing decade [22]. Moreover, Natoli et al recently reported that in Rome, Italy, an 18-year TNR program, including the monitoring of colonies by registered caretakers, has reduced the problem of immigration into colonies by abandoned cats and “spontaneous arrivals” (as noted by several of the same authors in 2006) to the point where now few “immigrated cats” replace cats that die or are removed for adoption [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the results attained on the UCF campus over a 28-year period most closely resemble what occurred contemporaneously on the waterfront in Newburyport, Massachusetts, where a long-term TNR program eliminated a population of an estimated 300 resident cats over a 17-year period; due to ongoing management, the results attained there have persisted over the ensuing decade [22]. Moreover, Natoli et al recently reported that in Rome, Italy, an 18-year TNR program, including the monitoring of colonies by registered caretakers, has reduced the problem of immigration into colonies by abandoned cats and “spontaneous arrivals” (as noted by several of the same authors in 2006) to the point where now few “immigrated cats” replace cats that die or are removed for adoption [25].…”
Section: Discussionmentioning
confidence: 99%
“…Nutter et al [28] reported that free-roaming female cats produce a mean of 1.4 litters per year, with a median of three kittens per litter (range, 1–6), and that expected kitten mortality before six months of age is as high as 75%. Consequently, as a result of UCF’s long-term TNR program, hundreds of kitten births were prevented, which likely avoided considerable suffering [25,28] and minimized preventable deaths [8], and along with adoption, made possible the significant and sustained decline of the community cat population over time.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, the control of the demography of unowned free-roaming cats (All domestic cats without an owner who have no constraints on their movements and on their breeding (reviewed in [1,2])), living in colonies in the urban environment, is regulated by the national law no. 281, enacted in 1991.…”
Section: Introductionmentioning
confidence: 99%
“…So far, in our country, despite the massive sterilization campaigns, there are few published papers on the results obtained, from a quantitative (see for example [2,3]) but especially from a qualitatively point of view, i.e., on the influence of neutering on either cat behaviour or on the social structure of cat colonies. In other words, despite the recent worldwide considerable examination in investigating and discussing TNR programs, the researches rarely focused on changes due to neutering in cat social relationships and in the resulting social structure of the cat group.…”
Section: Introductionmentioning
confidence: 99%
“…Estes animais podem ser classificados de acordo com o ambiente e seu estilo de vida em quatro parâmetros: 1nível de sociabilidade (ferais ou não ferais), segundo a OIE (Organização Mundial da Saúde Animal) para um animal feral é aquele foi domesticado que agora vive sem supervisão ou controle humano direto (CLERCQ, 2011), 2restrição (restritos: quando confinados em propriedades, abrigos ou lares adotivos; semi-restritos: animais que ocasionalmente recebem alimento, abrigo, e cuidados, se reproduzem livremente; e não restritos: quando não se encontram numa propriedade e não possuem supervisão direta de uma pessoa), 3guarda responsável e 4-local de permanência ou ambiente (KITTS-MORGAN, 2015). Dentro do grupo de animais não restritos encontram-se os ferais, que são aqueles não socializados que dificilmente poderiam ser integrados a um ambiente de convivência com humanos, inviabilizando cuidados o uma relação afetiva entre estes animais e o homen (SLATER, 2001) a origem dos animais ferais é diversa (NATOLI et al, 2019).…”
Section: -Capitulo 1 -Dinâmica Populacional E Aspectos Sanitários Deunclassified